PENGARUH BUDAYA ETIS ORGANISASI DAN INTEGRITAS TERHADAP KUALITAS AUDIT DENGAN SENSITIVITAS ETIKA AUDITOR SEBAGAI VARIABEL MODERASI PADA KANTOR AKUNTAN PUBLIK DI DENPASAR - Ni Putu Sintya Utami Dewi; Ni Komang Sumadi (UNHI Press, 2020)
The purpose of this study is to study and obtain evidence about the culture and organization associated with quality that is moderated by the ethical sensitivity of auditors at the Public Accounting Firm in Denpasar. Location of the study was conducted at the Public Accountant Office in Denpasar. The sampling technique used was purposive sampling, namely the determination of sampling with a specific purpose. Methods of data collection using questionnaires, interviews, observation and document recording. Testing the validity and reliability of the variables shows that the instrument variables are fully valid and reliable. The classic assumption test on the regression model shows that the data is normally distributed, does not contain heteroscedasticity and does not contain any multicollinearity.The results of the regression analysis show that the independent variables influence the variation of the variable preparation of financial statements (dependent). Hypothesis testing using the statistical test of t shows that the organizational ethical culture variable on audit quality shows the significance value of the t test of 0.020 which is smaller than Î± (real level) = 0.05, so it can be concluded that the organizational ethical culture is positive towards audit quality. Integrity variable on audit quality shows the significance value of t test of 0.019 which is smaller than Î± (real level) = 0.05, it can be concluded that the integration is positive for audit quality. The role of the auditor's ethical sensitivity in moderating the relationship of an organization's ethical culture to audit quality is approved by a significance value of 0.003 which concluded that the auditor's ethical sensitivity can strengthen the organizational ethical culture's relationship to audit quality. The role of the auditor's ethical sensitivity in moderating the relationship of integrity to audit quality is considered by a significance value of 0.038 which added to the ethical sensitivity of the auditor can increase the integrity competence of audit quality.